Didactic Possibilities of Using The Steam Educational Technology Tool In Teaching Natural Sciences on The Basis of an Integrative Approach - Ramazonovna, Khamidova (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2025)
This article reveals the didactic possibilities of STEAM educational technology based on an integrative approach in teaching natural sciences. The STEAM approach plays an important role in integrating students' interdisciplinary knowledge, acquiring practice-oriented knowledge, and developing critical thinking and problem-solving skills. The article provides scientific analyses of the application of modern pedagogical technologies to natural sciences and their effectiveness. So, provides feedback on the increase in the need for teaching natural sciences today, as well as on the further improvement of the system of teaching natural sciences and improving efficiency.